Design and formulation of an enteric-coated insulin nanoparticles for oral delivery / Mohd Hafiz Mohd Jaafar - Mohd Jaafar, Mohd Hafiz (2017)
Double-functional nanoparticles with pH-sensitivity and mucoadhesive were developed to prevent insulin from contacting the highly acidic medium in the stomach, prolong the intestinal residence time and increase the permeability of insulin to the systemic circulation. Four different formulations of enteric coated insulin nanoparticles were prepared using polyelectrolyte complexation and ionotropic gelation methods with varying concentrations of alginate and calcium chloride. Optimal gelation was achieved when concentration of alginate and calcium were 3.3 % w/w at pH 3.0. Formulation C containing of 11.630 % (v/v) insulin, 0.100 % (w/v) alginate, 0.045 % (w/v) Pluronic F-68, 0.035 % (w/v) dextran sulphate, 1.160 % (v/v) calcium chloride and 17.440 % (v/v) chitosan showed the best nanoparticle properties with droplet size of 333.27 ± 5.67 nm, polydispersity index of 0.24 ± 0.01 and zeta potential of-17.9 ± 0.98 mV, respectively. A reversed-phase high performance liquid chromatography (HPLC) method has been developed and validated for the qualification and quantification of insulin in rat plasma. The proposed method produced linear response over the concentration range of 0.39 to 50 ug/ml. The mean recovery was 99.6 %, while the coefficient of variation of within-day and betweenday measurements was less than 8 %. Their pharmacokinetic profiles were characterised after oral administration. Four groups of rat were administered orally with 100 m/kg of enteric-coated insulin nanoparticles while a control group was given lOmg/kg of pure insulin solution. Blood samples (200 ul) were collected using heparinised syringes at pre-determined time intervals over 240 min. 100 ul of plasma sample were introduced into HPLC and insulin concentration was measured at 210 nm. Pharmacokinetic profiles insulin in each group were calculated using trapezoidal method. Formulation C showed the highest absorption profile with AUC value of 2135.71 ± 68.64 fig/ml-min. The control group exhibited the lowest AUC value of 192.49 ± 10.92 ng/ml-min. In conclusion, delivery systems which exhibit pHsensitivity and mucoadhesive properties could have an excellent synergistic effect to enhance insulin absorption via oral delivery.